2016
DOI: 10.2807/1560-7917.es.2016.21.36.30334
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pertussis in Denmark, 1995 to 2013

Abstract: We describe incidence and age distribution of laboratory-confirmed pertussis in Denmark from 1995 to 2013. Notification has been mandatory since 2007. Since 1997, an acellular monocomponent vaccine has been used. The latest epidemic occurred in 2002 with an incidence of 36 per 100,000; since 1995, only six infant deaths have been recorded. The inter-epidemic incidence lies below 10 per 100,000. In 1995, the mean age of confirmed cases was 9.2 years (95% confidence interval (CI): 7.9–10.5; median: 5.1), this gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…Denmark and Finland have high similarities within the strains, excluding MLVA results ( Table 2). In addition, no outbreaks have been reported in these two countries 10 years prior to 2015 (a country-wide epidemic occurred in Denmark in 2016) (30,31). In the Netherlands, there has been a shift from BpSR3 to BpSR10, which is currently dominating.…”
Section: Discussionmentioning
confidence: 99%
“…Denmark and Finland have high similarities within the strains, excluding MLVA results ( Table 2). In addition, no outbreaks have been reported in these two countries 10 years prior to 2015 (a country-wide epidemic occurred in Denmark in 2016) (30,31). In the Netherlands, there has been a shift from BpSR3 to BpSR10, which is currently dominating.…”
Section: Discussionmentioning
confidence: 99%
“…While the measured seroincidence was 143 cases per 1000 person-years, the reported incidence was only 0.03 per 1000 person-years [35]. Dalby et al also reported laboratory-confirmed cases of pertussis in Denmark, from 1995 to 2013; in adults ≥50 years of age, the incidence of pertussis was stable in 2008-2011 (2/100,000 population), increased to 5/100,000 population in 2012 and then decreased again in 2013 (3/100,000 population) [36].…”
Section: Europementioning
confidence: 99%
“…However, unrecognized adult pertussis is also a significant factor contributing to the rise of pertussis cases among infants and children who are at more significant risks in developing more serious complications and even fatal infection [3,4,10,11]. The resurgence trend of pertussis incidence in all age groups, especially among adolescents and adults, were observed in most European countries and the USA for the past several years [12][13][14][15]. Older age individuals are often an asymptomatic carrier of pertussis; consequently, high transmission of pertussis to the vulnerable group and cause potential outbreak [16,17].…”
Section: Introductionmentioning
confidence: 99%